Enhancing heat transfer in compound twisted square ducts using shortened twisted tape inserts - Chithra V P; Balaji Bakthavatchalam; V. Jayakumar; Sambhaji Kusekar; A.K. Pandey; Khairul Habib; Salem Algarni; Talal Alqahtani (Results in Engineering)
Enhancing heat transfer is an important area in various forms of energy conservation that is closely related to economically efficient systems. A typical technique for improving heat transfer in thermal systems is the use of tape inserts. The majority of research on tape inserts has concentrated on straight tubes and ducts. This research offers insights into optimizing heat exchanger design using twisted square ducts. A thorough analysis of the thermal-hydraulic performance of the twisted square duct having short-length twisted tape inserts of varying lengths under laminar flow conditions is investigated numerically. Length ratio is varied across the values of 0.2, 0.4, 0.6, 0.8 and 1. ANSYS Fluent is employed to numerically solve the governing equations and SIMPLE algorithm for pressure-velocity coupling. The numerical analysis is conducted using constant wall temperature as the boundary condition. The accuracy of the results obtained is confirmed by validation against the published experimental result. Findings obtained show that, inserting twisted tapes of varying lengths into the twisted square duct improves heat transfer rate and pressure drop compared with the plain twisted square duct. Although a length ratio of 1 has a better rate of heat transfer than those with length ratios of 0.2, 0.4, 0.6, and 0.8, the increased friction factor leads to less thermal efficiency. The present study discovered that a twisted tape with a length ratio of 0.2 produces the best thermal performance in the laminar regime. The thermal performance factor reaches its peak at 1.45, corresponding to the Reynolds number 1250 for a length ratio of 0.2 case. For length ratio 1, the Reynolds number 500 has the lowest thermal performance factor value of 1.11. These findings will help to improve the efficiency and performance of heat exchangers, thereby enabling the design of more efficient heat exchange systems.